Athlete Activism Contemporary Perspectives - Magrath, Rory (Routledge Research in Sport, Culture and Society, 2022)
This book examines the phenomenon of athlete activism across all levels of sport, from elite and international sport, to collegiate and semi-pro, and asks what this tells us about the relationship between sport and wider society. With contributions from scholars around the world, the book presents a series of fascinating case studies, including the activism of world-famous athletes such as Serena Williams, Megan Rapinoe and Raheem Sterling. Covering a broad range of sports, from the National Football League (NFL) and Australian Rules, to fencing and the Olympic Games, the book sheds important light on some of the most important themes in the study of sport, including gender, power, racism, intersectionality and the rise of digital media. It also considers the financial impact on athletes when they take a stand and the psychological impact of activism and how that might relate to sports performance. It has never been the case that 'sport and politics don't mix', and now, more than ever, the opposite is true. This is essential reading for anybody with an interest in the politics or sociology of sport, the politics of protest, social movements or media studies.